2014
DOI: 10.1021/nn5003776
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nanowire Optical Cavities as Efficient Photon Absorbers

Abstract: Recent investigations of semiconductor nanowires have provided strong evidence for enhanced light absorption, which has been attributed to nanowire structures functioning as optical cavities. Precise synthetic control of nanowire parameters including chemical composition and morphology has also led to dramatic modulation of absorption properties. Here we report finite-difference time-domain (FDTD) simulations for silicon (Si) nanowire cavities to elucidate the key factors that determine enhanced light absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 39 publications
2
74
0
1
Order By: Relevance
“…Materials with a large surface area-tovolume ratio can be a good candidate in optoelectronics applications. Applications of devices based on optical properties can include lasers, solar cells, optical detectors and sensors, displays, photo-catalysis, imaging and phosphor devices [23][24][25][26][27][28][29][30].…”
Section: Low Dimensional Nanostructuresmentioning
confidence: 99%
“…Materials with a large surface area-tovolume ratio can be a good candidate in optoelectronics applications. Applications of devices based on optical properties can include lasers, solar cells, optical detectors and sensors, displays, photo-catalysis, imaging and phosphor devices [23][24][25][26][27][28][29][30].…”
Section: Low Dimensional Nanostructuresmentioning
confidence: 99%
“…Despite the antennaeffect-mediated strong absorption at short wavelengths, the overall performance of SNSCs is still far from expectation due to the narrow resonant bands and the relatively low absorption at long wavelengths. To improve the lightharvesting performance, properly engineering the structure parameters and cross-sectional morphology of the nanowires has been widely discussed in recent literatures [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It was shown that the light absorption in nanowire devices could be effectively engineered through control over the size, geometry and orientation of the nanostructure [8].…”
Section: Introductionmentioning
confidence: 99%
“…특히, 이러한 구조를 기반으로 하는 반도체 물질은, 극대화된 부피 대 표면적과 광학적 및 전 기화학적 특징으로 인하여 수많은 응용 소자로 이 용되어져 왔다 2,3) . 특히 산화물 반도체 의 경우, 각 종 화학 가스에 민감하게 반응하여 그 전기적 특성 이 변화하는데, 이러한 특징으로 인하여 각종 가스 센서의 응용이 활발히 연구되고 있다 [4][5][6] .…”
Section: 서 론 1차원 구조의 나노 물질은 그 독특한 물리적 특 성으로 인하여 최근 수십 년 간 많은 관심을 받아 왔unclassified